A heavy metal ion adsorption material and preparation method thereof

By embedding FAPTO in high-strength permeable porous materials made of medical waste slag and inorganic gelling materials, the problem of FAPTO dispersing in natural water bodies is solved, the effect of efficient adsorption and collection of heavy metal ions is achieved, and the resource utilization of medical waste slag is promoted.

CN116059970BActive Publication Date: 2025-04-08SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202111282441.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-01
Publication Date
2025-04-08
Estimated Expiration
2041-11-01

AI Technical Summary

Technical Problem

The existing high-efficiency heavy metal ion adsorption material FAPTO is easily dispersed when used alone in natural water bodies, affecting the collection of heavy metal ions.

Method used

Amorphous phosphorylated titanium oxide (FAPTO) is embedded and fixed in the void of permeable porous material with a certain strength. The specific method is to mix FAPTO with medical waste slag and inorganic gelling material, and then hardened and organically coated to form a high-strength permeable porous material.

Benefits of technology

It realizes the stable existence of FAPTO in porous materials, improves the adsorption and collection efficiency of heavy metal ions, and effectively utilizes medical waste slag, achieving the goal of turning waste into treasure.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to a heavy metal ion adsorption material and a preparation method thereof. The heavy metal ion adsorption material comprises: a porous organic composite matrix, and an amorphous TiPO adsorbent distributed in the pores of the porous organic composite matrix; the porous organic composite matrix is ​​obtained by solidifying medical waste slag and an inorganic gelling material, and the medical waste slag is a metal oxide or / and a carbonate; preferably, the content of the amorphous TiPO adsorbent accounts for 0.5 to 3 wt% of the total mass of the heavy metal ion adsorption material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a heavy metal ion adsorption material and a preparation method thereof, and in particular to a method for preparing the heavy metal ion adsorption material using medical waste slag as a main material, and belongs to the technical field of solid waste resource utilization. Background Art

[0002] With the improvement of science and technology, my country's industry has developed rapidly, which has continuously improved people's living standards. However, the development of industry has also put pressure on my country's ecological environment: the amount of untreated industrial wastewater directly discharged into the natural environment is increasing, which destroys the self-purification capacity of water bodies and causes the content of heavy metal pollutants in water bodies to exceed the standard, causing harm to the life of aquatic organisms and agricultural production. Therefore, the problem of heavy metal pollution in water bodies cannot be ignored.

[0003] After years of technical research, Huang Fuqiang's research group at the Shanghai Institute of Ceramics has invented a highly efficient heavy metal ion adsorption material: amorphous phosphated titanium oxide (FAPTO) (application number: 201710452750.6). This material has an adsorption efficiency of over 99% for heavy metal ions in water. However, this material is porous and has a very low bulk density. It is easy to drift when used alone in natural water bodies, thus affecting the collection of heavy metal ions. Summary of the invention

[0004] In order to enable FAPTO to effectively adsorb and collect heavy metal ions in water, the present invention embeds and fixes amorphous phosphated titanium oxide in the gaps of a water-permeable porous material with a certain strength, and provides a heavy metal ion adsorption material and a preparation method thereof.

[0005] On the one hand, the present invention provides a heavy metal ion adsorption material, comprising: a porous organic composite matrix, and an amorphous TiPO adsorbent distributed in the pores of the porous organic composite matrix; the porous organic composite matrix is ​​obtained by solidifying medical waste slag and an inorganic gelling material, and the medical waste slag is a metal oxide and / or a carbonate; preferably, the content of the amorphous TiPO adsorbent accounts for 0.5 to 3 wt% of the total mass of the heavy metal ion adsorption material.

[0006] In the present invention, the main components of medical waste slag are inorganic non-metallic materials (metal oxides and / or carbonates, such as aluminum oxide, iron oxide, silicon oxide, magnesium oxide and calcium carbonate, etc.), which are not hazardous wastes and have great potential for resource utilization. Slag is chemically stable and insoluble in water after high-temperature treatment, and is a good raw material for preparing porous materials. We use slag as the main raw material to prepare high-strength water-permeable porous materials, which not only enables FAPTO to effectively play the role of adsorbing and collecting heavy metal ions, but also can effectively utilize medical waste slag to achieve the purpose of turning waste into treasure.

[0007] Preferably, the inorganic gelling material is cement; the mass ratio of the inorganic gelling material to medical waste slag is (1-5):1.

[0008] Preferably, the porosity of the heavy metal ion adsorption material is 30% to 50%, preferably 40%.

[0009] Preferably, the aperture size is 500 μm to 3 mm, preferably 1 mm to 3 mm.

[0010] Preferably, the amorphous TiPO adsorbent is composed of amorphous TiPO particles; the particle size of the amorphous TiPO particles is 100 nm to 5 μm.

[0011] Preferably, the strength of the heavy metal ion adsorption material is 10 to 35 MPa.

[0012] In another aspect, the present invention provides a method for preparing a heavy metal ion adsorbent material, comprising:

[0013] (1) adding water to medical waste slag and inorganic gelling material to mix them to prepare a paste-like raw material;

[0014] (2) The amorphous TiPO adsorbent and the obtained paste raw material are mixed, and then placed in air to harden for 14 to 28 days to obtain the heavy metal ion adsorbent.

[0015] Preferably, the mass of the amorphous TiPO adsorbent is 5% to 20wt% of the paste raw material.

[0016] Preferably, the mass of the water is 10wt% to 30wt% of the total mass of the medical waste slag and the inorganic gelling material.

[0017] In another aspect, the present invention provides a method for preparing a heavy metal ion adsorbent material, comprising:

[0018] (1) adding water to medical waste slag and inorganic gelling material to mix them to prepare a paste-like raw material;

[0019] (2) mixing the amorphous TiPO adsorbent and the organic coating material, melting and stirring at 80° C. to 100° C. for 20 to 60 minutes, and crushing and sieving after cooling to obtain an organic powder of 40 to 80 mesh;

[0020] (3) Mixing the organic powder and the obtained paste raw material, placing them in the air to harden for 14 to 28 days, immersing them in an organic solution to remove the organic coating material, and then washing and drying to obtain the heavy metal ion adsorption material. Adding the organic coating material can protect the functional groups of FAPTO so that they are not changed or destroyed during the hardening process of the inorganic gelling material. In addition, the organic coating material is also an effective pore-forming material. After being dissolved by an organic solvent, pores will be formed. This structure will increase the adsorption efficiency of FAPTO for heavy metal ions.

[0021] Preferably, the mass of the water is 10wt% to 30wt% of the total mass of the medical waste slag and the inorganic gelling material.

[0022] Preferably, in step (2), the organic coating material is selected from at least one of paraffin wax, microcrystalline wax and beeswax; preferably, the mass of the organic coating material is 10 to 20 times the mass of the amorphous TiPO adsorbent.

[0023] Preferably, the mass of the organic powder is 5% to 20wt% of the paste raw material.

[0024] Preferably, in step (3), the organic solvent is at least one of ether, aviation kerosene, n-hexane, n-heptane and tribromopropane; the mass of the organic solvent is 1 to 10 times that of the hardened composite material, and the immersion time is 4 to 12 hours.

[0025] Beneficial effects:

[0026] The invention relates to a preparation method of a heavy metal ion adsorption material using medical waste slag as a main raw material, comprising: organically coating FAPTO with high-efficiency heavy metal ion adsorption performance, then compounding the coated organic particles and the treated medical waste slag powder in a porous inorganic gelling material, soaking the porous inorganic gelling material in an organic solvent after molding, dissolving an organic wax film on the surface of FAPTO, and then drying the organic solvent in an oven, so as to prepare a usable material with heavy metal ion adsorption performance. BRIEF DESCRIPTION OF THE DRAWINGS DETAILED DESCRIPTION

[0027] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.

[0028] In the present disclosure, a preparation method of a heavy metal ion adsorption material is provided by selecting medical waste slag as a main raw material.

[0029] The following is an exemplary description of the preparation method of the heavy metal ion adsorbing material.

[0030] The preparation process of amorphous TiPO adsorbent (FAPTO) refers to the prior patent (application number 201710452750.6).

[0031] The surface of FAPTO with high heavy metal ion adsorption performance is organically coated and then broken into organic particles. The main organic matter (organic coating material) used for coating is one or more of paraffin, microcrystalline wax, and beeswax. The mass of the coated organic matter is 10 to 20 times the mass of the adsorbent. If there is too little organic coating material, the coating effect is not good, and if there is too much organic coating material, there is too little FAPTO in the composite material, which affects the adsorption efficiency of the sample.

[0032] As a method of preparing the organic coating material, the organic coating material is melted at 80°C to 100°C, and then the amorphous TiPO adsorbent is added to the molten organic matter and stirred for 20min to 60min. After cooling, the mixture is broken up and an organic powder of 40-80 mesh is obtained by sieving.

[0033] A certain proportion of medical waste slag and inorganic gelling material are mixed with water to make a paste raw material. The inorganic gelling material used is cement. The slag is a powder that is crushed and sieved through a 60-mesh screen. The mass of cement can be 1 to 5 times the mass of medical waste slag. The mass of water is 10wt% to 30wt% of the total mass of medical waste slag and inorganic gelling material. After the water, medical waste slag and inorganic gelling material are mixed, continue to stir in a mixer for 5 to 20 minutes.

[0034] Mix the organic powder and the paste raw material to obtain a slurry. The mass of the organic particles is 5% to 20% of the mass of the paste raw material, and the two are stirred in a stirrer for 10 to 30 minutes. Alternatively, the amorphous TiPO adsorbent and the paste raw material are directly mixed to obtain a slurry. The mass of the amorphous TiPO adsorbent is 5% to 20% of the mass of the paste raw material, and the two are stirred in a stirrer for 10-30 minutes.

[0035] The mixed slurry is left to harden in air for 14 to 28 days.

[0036] The hardened material is soaked and washed in an organic solvent. The washed material is then dried in an oven to obtain a material with heavy metal ion adsorption performance. The organic solvent used is one or more of ether, aviation kerosene, n-hexane, n-heptane or tribromopropane. The mass of the organic solvent is 1 to 10 times that of the composite material, and the soaking time is 4 to 12 hours. The number of washings can be 3 to 5 times. The drying temperature can be 80 to 100°C, and the drying time can be 2 to 10 hours.

[0037] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values ​​​​exemplified below.

[0038] Example 1

[0039] 1) Weigh 50 g of 58# semi-refined paraffin wax, place it in a heated beaker and melt it at 100°C, then add 3.0 g of FAPTO and stir for 30 min;

[0040] 2) Cool the mixture, crush it with a dispersion disk, pass the crushed powder through 40 and 80 mesh sieves, and take the part with particle size range between 40-80 mesh;

[0041] 3) crush the medical waste slag with a ball mill, pass it through a 60-mesh sieve, weigh 30 grams of the sieved slag, then weigh 30 grams of cement, mix the slag and cement, add 10 grams of water and stir evenly;

[0042] 4) taking 5 g of the organic particles prepared in step 2), and stirring the organic particles and the paste-like inorganic mixture obtained in step 3 in a stirrer for 10-30 min;

[0043] 5) placing the mixture prepared in step 4) in a plastic mold, sealing it after compaction, and placing it for 14 days;

[0044] 6) Soaking the block material with higher strength prepared in step 5) in n-heptane, the mass of n-heptane is 100 g, and the soaking time is 4 h;

[0045] 7) taking out the material etched with n-heptane in step 6) and washing it with pure n-heptane solvent for 3 times;

[0046] 8) Drying the washed material in step 7) at 80° C. for 4 hours to obtain a material that can be used to adsorb heavy metal ions in water. The content of amorphous TiPO adsorbent in the obtained heavy metal ion adsorption material accounts for 0.5% of the total mass of the heavy metal ion adsorption material, the porosity is 35%, and the pore size distribution is 1 mm to 3 mm.

[0047] 9) The compressive strength of the material prepared in this example is 17MPa. 2+ After being placed in a solution with a concentration of 54 mg / L for 12 hours, the concentration of heavy metal ions in the solution can be reduced to 0.1 mg / L.

[0048] Example 2

[0049] 1) Weigh 50 g of 58# semi-refined paraffin wax, place it in a heated beaker and melt it at 100°C, then add 3.0 g of FAPTO and stir for 30 min;

[0050] 2) Cool the mixture, crush it with a dispersion disk, pass the crushed powder through 40 and 80 mesh sieves, and take the part with particle size range between 40-80 mesh;

[0051] 3) crush the medical waste slag with a ball mill, pass it through a 60-mesh sieve, weigh 20 grams of the sieved slag, then weigh 40 grams of cement, mix the slag and cement, add 10 grams of water and stir evenly;

[0052] 4) taking 10 g of the organic particles prepared in step 2), and stirring the organic particles and the paste-like inorganic mixture obtained in step 3 in a stirrer for 10-30 min;

[0053] 5) placing the mixture prepared in step 4) in a plastic mold, sealing it after compaction, and placing it for 14 days;

[0054] 6) Soaking the block material with higher strength prepared in step 5) in n-heptane, the mass of n-heptane is 100 g, and the soaking time is 4 h;

[0055] 7) taking out the material etched with n-heptane in step 6) and washing it with pure n-heptane solvent for 3 times;

[0056] 8) Drying the washed material in step 7) at 80° C. for 4 hours to obtain a material that can be used to adsorb heavy metal ions in water. The content of amorphous TiPO adsorbent in the obtained heavy metal ion adsorption material accounts for 1% of the total mass of the heavy metal ion adsorption material, the porosity is 45%, and the pore size distribution is 1 mm to 5 mm;

[0057] 9) The compressive strength of the material prepared in this example is 18 MPa.

[0058] Example 3

[0059] 1) Weigh 50 g of microcrystalline wax, place it in a heated beaker and melt it at 100°C, then add 3.0 g of FAPTO and stir for 30 min;

[0060] 2) Cool the mixture, crush it with a dispersion disk, pass the crushed powder through 60 and 80 mesh sieves, and take the part with particle size range between 60-80 mesh;

[0061] 3) crush the medical waste slag with a ball mill, pass it through a 60-mesh sieve, weigh 40 grams of the sieved slag, then weigh 20 grams of cement, mix the slag and cement, add 10 grams of water and stir evenly;

[0062] 4) taking 5 g of the organic particles prepared in step 2), and stirring the organic particles and the paste-like inorganic mixture obtained in step 3 in a stirrer for 10-30 min;

[0063] 5) placing the mixture prepared in step 4) in a plastic mold, sealing it after compaction, and placing it for 28 days;

[0064] 6) Soaking the block material with higher strength prepared in step 5) in n-heptane, the mass of n-heptane is 100 g, and the soaking time is 8 h;

[0065] 7) taking out the material etched with n-heptane in step 6) and washing it with pure n-heptane solvent for 3 times;

[0066] 8) Drying the washed material in step 7) at 80° C. for 4 hours to obtain a material that can be used to adsorb heavy metal ions in water. The content of amorphous TiPO adsorbent in the obtained heavy metal ion adsorption material accounts for 0.5% of the total mass of the heavy metal ion adsorption material, the porosity is 40%, and the pore size distribution is 0.5 mm to 3 mm;

[0067] 9) The compressive strength of the material prepared in this example is 16 MPa.

[0068] Example 4

[0069] 1) The medical waste slag is crushed by ball mill, passed through a 60-mesh sieve, 40 grams of the sieved slag is weighed, and then 20 grams of cement is weighed, the slag and cement are mixed, and 10 grams of water is added to stir evenly;

[0070] 2) Take 0.6 g of FAPTO and stir it and the paste-like inorganic mixture obtained in step 3 in a stirrer for 10-30 min;

[0071] 3) placing the mixture prepared in step 4) in a plastic mold, sealing and placing for 28 days after shaking, wherein the content of amorphous TiPO adsorbent in the obtained heavy metal ion adsorbent material accounts for 1% of the total mass of the heavy metal ion adsorbent material, the porosity is 15%, and the pore size distribution is 0.5 mm to 1 mm;

[0072] 4) The samples prepared in this batch were 2+ After being placed in a solution with a concentration of 54 mg / L for 12 hours, the concentration of heavy metal ions in the solution can be reduced to 0.9 mg / L.

[0073] Example 5

[0074] 1) Weigh 60 g of 58# semi-refined paraffin, place it in a heated beaker and melt it at 90°C, then add 3.0 g of FAPTO and stir for 30 min;

[0075] 2) Cool the mixture, crush it with a dispersion disk, pass the crushed powder through 60 and 80 mesh sieves, and take the part with particle size range between 60-80 mesh;

[0076] 3) crush the medical waste slag with a ball mill, pass it through a 60-mesh sieve, weigh 30 grams of the sieved slag, then weigh 30 grams of cement, mix the slag and cement, add 10 grams of water and stir evenly;

[0077] 4) taking 6 grams of the organic particles prepared in step 2), and stirring the organic particles and the paste-like inorganic mixture obtained in step 3 in a stirrer for 10-30 minutes;

[0078] 5) placing the mixture prepared in step 4) in a plastic mold, sealing it after compaction, and placing it for 28 days;

[0079] 6) Soaking the block material with high strength prepared in step 5) in aviation kerosene, the mass of the aviation kerosene is 150 grams, and the soaking time is 8 hours;

[0080] 7) taking out the material etched with n-heptane in step 6) and washing it with aviation kerosene for 3 times;

[0081] 8) Drying the washed material in step 7) at 80°C for 4 hours to obtain a material that can be used to adsorb heavy metal ions in water. The content of amorphous TiPO adsorbent in the obtained heavy metal ion adsorption material accounts for 0.5% of the total mass of the heavy metal ion adsorption material, the porosity is 48%, and the pore size distribution is 0.5 mm to 5 mm;

[0082] 9) The samples prepared in this batch were 2+ After being placed in a solution with a concentration of 54 mg / L for 12 hours, the concentration of heavy metal ions in the solution can be reduced to 0.1 mg / L.

[0083] Example 6

[0084] 1) Weigh 40 g of 58# semi-refined paraffin, place it in a heated beaker and melt it at 90°C, then add 3.0 g of FAPTO and stir for 30 min;

[0085] 2) Cool the mixture, crush it with a dispersion disk, pass the crushed powder through 60 and 80 mesh sieves, and take the part with particle size range between 60-80 mesh;

[0086] 3) crush the medical waste slag with a ball mill, pass it through a 60-mesh sieve, weigh 30 grams of the sieved slag, then weigh 30 grams of cement, mix the slag and cement, add 10 grams of water and stir evenly;

[0087] 4) taking 5 g of the organic particles prepared in step 2), and stirring the organic particles and the paste-like inorganic mixture obtained in step 3 in a stirrer for 10-30 min;

[0088] 5) placing the mixture prepared in step 4) in a plastic mold, sealing it after compaction, and placing it for 28 days;

[0089] 6) Soaking the block material with high strength prepared in step 5) in aviation kerosene, the mass of the aviation kerosene is 150 grams, and the soaking time is 8 hours;

[0090] 7) taking out the material etched with n-heptane in step 6) and washing it with aviation kerosene for 3 times;

[0091] 8) Drying the washed material in step 7) at 80°C for 4 hours to obtain a material that can be used to adsorb heavy metal ions in water. The content of amorphous TiPO adsorbent in the obtained heavy metal ion adsorption material accounts for 0.6% of the total mass of the heavy metal ion adsorption material, the porosity is 40%, and the pore size distribution is 0.5 mm to 5 mm;

[0092] 9) The samples prepared in this batch were 2+ After being placed in a solution with a concentration of 54 mg / L for 12 hours, the concentration of heavy metal ions in the solution can be reduced to 0.15 mg / L.

[0093] Example 7

[0094] 1) Weigh 30 g of 58# semi-refined paraffin, place it in a heated beaker and melt it at 90°C, then add 3.0 g of FAPTO and stir for 30 min;

[0095] 2) Cool the mixture, crush it with a dispersion disk, pass the crushed powder through 60 and 80 mesh sieves, and take the part with particle size range between 60-80 mesh;

[0096] 3) crush the medical waste slag with a ball mill, pass it through a 60-mesh sieve, weigh 30 grams of the sieved slag, then weigh 30 grams of cement, mix the slag and cement, add 10 grams of water and stir evenly;

[0097] 4) taking 6 grams of the organic particles prepared in step 2), and stirring the organic particles and the paste-like inorganic mixture obtained in step 3 in a stirrer for 10-30 minutes;

[0098] 5) placing the mixture prepared in step 4) in a plastic mold, sealing it after compaction, and placing it for 28 days;

[0099] 6) Soaking the block material with high strength prepared in step 5) in aviation kerosene, the mass of the aviation kerosene is 150 grams, and the soaking time is 8 hours;

[0100] 7) taking out the material etched with n-heptane in step 6) and washing it with aviation kerosene for 3 times;

[0101] 8) Drying the washed material in step 7) at 80° C. for 4 hours to obtain a material that can be used to adsorb heavy metal ions in water. The content of amorphous TiPO adsorbent in the obtained heavy metal ion adsorption material accounts for 1% of the total mass of the heavy metal ion adsorption material, the porosity is 30%, and the pore size distribution is 0.5 mm to 3 mm;

[0102] 9) The samples prepared in this batch were 2+ After being placed in a solution with a concentration of 54 mg / L for 12 hours, the concentration of heavy metal ions in the solution can be reduced to 0.1 mg / L.

Claims

1. A method for preparing a heavy metal ion adsorbent material, characterized in that: The heavy metal ion adsorption material comprises: a porous organic composite matrix, and an amorphous TiPO adsorbent distributed in the pores of the porous organic composite matrix; the porous organic composite matrix is ​​obtained by solidifying medical waste slag and an inorganic gelling material, and the medical waste slag is a metal oxide and / or a carbonate; the content of the amorphous TiPO adsorbent accounts for 0.5 to 3 wt% of the total mass of the heavy metal ion adsorption material; the preparation method of the heavy metal ion adsorption material comprises the following steps: (1) adding water to medical waste slag and an inorganic gelling material to mix them to prepare a paste-like raw material, wherein the inorganic gelling material is cement; the mass ratio of the inorganic gelling material to the medical waste slag is (1-5):1; (2) Mixing an amorphous TiPO adsorbent and an organic coating material, melting and stirring at 80°C to 100°C for 20 minutes to 60 minutes, and crushing and sieving after cooling to obtain an organic powder of 40 to 80 mesh; the amorphous TiPO adsorbent is composed of amorphous TiPO particles; the particle size of the amorphous TiPO particles is 0.1 μm to 5 μm; the organic coating material is selected from at least one of paraffin, microcrystalline wax and beeswax; the mass of the organic coating material is 10 to 20 times the mass of the amorphous TiPO adsorbent; (3) Mixing the organic powder and the obtained paste raw material, placing them in the air to harden for 14 to 28 days, immersing them in an organic solution to remove the organic coating material, and then washing and drying to obtain the heavy metal ion adsorption material; wherein the mass of the organic powder is 5% to 20wt% of the paste raw material.

2. The preparation method according to claim 1, characterized in that: The porosity of the heavy metal ion adsorption material is 30% to 50%; the size of the pore size is 500 μm to 3 mm.

3. The preparation method according to claim 2, characterized in that: The porosity of the heavy metal ion adsorption material is 40%; the size of the pore size is 1 mm to 3 mm.

4. The preparation method according to any one of claims 1 to 3, characterized in that The compressive strength of the heavy metal ion adsorption material is 10 to 35 MPa.

5. The preparation method according to any one of claims 1 to 3, characterized in that: In step (1), the mass of the water is 10wt% to 30wt% of the total mass of the medical waste slag and the inorganic gelling material.

6. The preparation method according to any one of claims 1 to 3, characterized in that: In step (3), the organic solution is at least one of ether, aviation kerosene, n-hexane, n-heptane and tribromopropane; the mass of the organic solution is 1 to 10 times that of the hardened composite material, and the immersion time is 4 to 12 hours.

Citation Information

Patent Citations

  • A method for efficiently preparing porous, high specific surface area amorphous TiPO

    CN107394257B

  • Preparation method of adsorption and catalysis material for removing heavy metals and organic pollutants in municipal sludge

    CN104096540A

  • Preparation method of dephosphorization stuffing and dephosphorization equipment filled with stuffing

    CN106083180A

  • Metallurgical solid waste based pressed active carbon for desulfurization and denitrification of flue gas and preparation method of pressed active carbon

    CN108745282A

  • Titanium dioxide based porous block as well as preparation method and application thereof

    CN108772052A